Relationship between Income Tax Withholding Article 23 and Fiscal Reconciliation Case Study at PT. SFM - Novi Fitriani; Suriai Lafau; Sarah Obadia Ivana; Zikra Nurul Annisah; Licerman Hulu; Galih Supraja (International Journal of Economic Research and Financial Accounting, 2025)
This study investigates the relationship between the withholding of Income Tax Article 23 (PPh 23) and fiscal reconciliation at PT. SFM, a company operating in Indonesia. Withholding PPh 23 is a critical component of corporate tax compliance, particularly in service transactions. Failure to comply accurately may result in positive fiscal corrections and increase corporate tax liabilities. Utilizing a case study approach with descriptive quantitative methods, the research draws on primary data from interviews with tax and accounting personnel and secondary data from financial statements and withholding tax records for the 2023 fiscal year. The findings reveal significant inaccuracies in PPh 23 withholdings on service-related expenses, leading to a positive fiscal adjustment of IDR 470,000,000. This adjustment directly impacted taxable income and overall corporate tax obligations. Contributing factors include insufficient internal controls and limited staff comprehension of tax regulations. The study emphasizes the necessity for enhanced internal governance and staff capacity-building to ensure accurate tax compliance and mitigate fiscal risks.